O que revelar? o que esconder? imprensa & maçonaria no findar do dezenove (Pará, 1872-1892) - SANTOS, Alan Christian de Souza (Universidade Federal do Pará, 2014)
The performance masonic in the press of Para in the nineteenth century is seen in this dissertation from the counterpoint between the reveal and hide. Stand out, above all, two distinct moments of the same transaction. At first, the masonry abandons his reserved attitude and decides to create an official newspaper (O Pelicano) for to do a front in the dictates ultramontanos (A Boa Nova). And, in the second, it returns to your initial condition to suspend the circulation of publication, but without necessarily go out from the journalistic media. So that secret and publicity were intermingled in the "voices" of the institution representatives. The research allowed the nominal identification of a extensive group of masons and brought off to demonstrate a few tensions and conflicts that sometimes closed up them like a "brothers" and sometimes definitely put them on opposite sides of the press, in stores, on life. Taking into account the social changes (Abolition) and political (Republic) that occurred along the temporality accosted, this study also discusses the way in which the discourses, practices and representations of Pará masons were articulated with the transformations that simultaneously to get at the province of Para and imperial society.